Seismic Vulnerability Assessment of Typical Stone Masonry Building - Paudel, Kshitiz (Journal of Innovations in Engineering Education, 2020)
Masonry, the most commonly used building typology is the building of structures from individual units, which are often laid in and bound together by mortar. Masonry structures are the most vulnerable with external forces. Nepal is disaster prone zone and get frequently attack by various hazard such as earthquake, wind storms, flash-floods, fire, landslides, heavy rain fall, lightening and many more. So, in order to maintain resistive structures, seismic vulnerability of structure should be examined. Nepal Population and housing Census 2011, total 3350143 (2,397,441 –Mud bonded bricks/stone and 952,702- Cement Bonded bricks/ stone) houses out of 5423297 (61.77%) are found to be have masonry foundations. So, to link the context of Resistance structures in Nepal’s context first of all, the predominating stone masonry spread widely over Nepal must be checked for their seismic vulnerability. So, a typical residential stone masonry building is taken for this study. Seismic Vulnerability of the Building is examined in accordance with guidance provided by Government of Nepal- Ministry of Physical Planning and Works, 2011 in their guideline which describe the procedure for qualitative and quantitative assessment of structural earthquake vulnerability of public and private buildings in Nepal. Furthermore, Building is modelled and analyzed by using ETABS software. The outcome obtained from ETABS software are used to find the condition of building and to propose method for its strengthening.